Studies on Schismatoglottideae (Araceae) of Borneo XXXXIII: Fenestratarum culum - A new genus and species from Kalimantan Barat, Indonesian Borneo - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2014)
Fenestratarum is described as a new genus of Tribe Schismatoglottideae, with a single novel species, Fenestratarum culum. Preliminary molecular analyses places Fenestratarum near the base of a clade comprised of Bakoa, Hottarum, two clades containing species currently assigned to Aridarum, and a clade of species presently included in Piptospatha.